Role of cytokines in rheumatoid arthritis. - Feldmann, M; Brennan, F; Maini, R (1996)
Analysis of cytokine mRNA and protein in rheumatoid arthritis tissue revealed that many proinflammatory cytokines such as TNF alpha, IL-1, IL-6, GM-CSF, and chemokines such as IL-8 are abundant in all patients regardless of therapy. This is compensated to some degree by the increased production of anti-inflammatory cytokines such as IL-10 and TGF beta and cytokine inhibitors such as IL-1ra and soluble TNF-R. However, this upregulation in homeostatic regulatory mechanisms is not sufficient as these are unable to neutralize all the TNF alpha and IL-1 produced. In rheumatoid joint cell cultures that spontaneously produce IL-1, TNF alpha was the major dominant regulator of IL-1. Subsequently, other proinflammatory cytokines were also inhibited if TNF alpha was neutralized, leading to the new concept that the proinflammatory cytokines were linked in a network with TNF alpha at its apex. This led to the hypothesis that TNF alpha was of major importance in rheumatoid arthritis and was a therapeutic target. This hypothesis has been successfully tested in animal models, of, for example, collagen-induced arthritis, and these studies have provided the rationale for clinical trials of anti-TNF alpha therapy in patients with long-standing rheumatoid arthritis. Several clinical trials using a chimeric anti-TNF alpha antibody have shown marked clinical benefit, verifying the hypothesis that TNF alpha is of major importance in rheumatoid arthritis. Retreatment studies have also shown benefit in repeated relapses, indicating that the disease remains TNF alpha dependent. Overall these studies demonstrate that analysis of cytokine expression and regulation may yield effective therapeutic targets in inflammatory disease.